Self-processing in coma, unresponsive wakefulness syndrome and minimally conscious state - Ferré, Fabrice; Heine, Lizette; Naboulsi, Edouard; Gobert, Florent; Beaudoin-Gobert, Maude; Dailler, Frédéric; Buffières, William; Corneyllie, Alexandra; Sarton, Benjamine; Riu, Béatrice; Luauté, Jacques; Silva, Stein; et al. (Frontiers in Human Neuroscience, 2023)
Behavioural and cerebral dissociation has been now clearly established in some patients with acquired disorders of consciousness (DoC). Altogether, these studies mainly focused on the preservation of high-level cognitive markers in prolonged DoC, but did not specifically investigate lower but key-cognitive functions to consciousness emergence, such as the ability to take a first-person perspective, notably at the acute stage of coma. We made the hypothesis that the preservation of self-recognition (i) is independent of the behavioural impairment of consciousness, and (ii) can reflect the ability to recover consciousness. Hence, using bedside EEG recordings, we acquired, in a large cohort of 129 severely brain damaged patients, the brain response to the passive listening of the subject’s own name (SON) and unfamiliar other first names (OFN). One hundred and twelve of them (mean age ± SD = 46 ± 18.3 years, sex ratio M/F: 71/41) could be analyzed for the detection of an individual and significant discriminative P3 event-related brain response to the SON as compared to OFN (‘SON effect’, primary endpoint assessed by temporal clustering permutation tests). Patients were either coma (n=38), unresponsive wakefulness syndrome (UWS, n=30) or minimally conscious state (MCS, n=44), according to the revised version of the Coma Recovery Scale (CRS-R). Overall, 33 DoC patients (29%) evoked a ‘SON effect’. This electrophysiological index was similar between coma (29%), MCS (23%) and UWS (34%) patients (p=0.61). MCS patients at the time of enrolment were more likely to emerged from MCS (EMCS) at 6 months than coma and UWS patients (p=0.013 for comparison between groups). Among the 72 survivors’ patients with event-related responses recorded within 3 months after brain injury, 75% of the 16 patients with a SON effect were EMCS at 6 months, while 59% of the 56 patients without a SON effect evolved to this favourable behavioural outcome. About 30% of severely brain-damaged patients suffering from DoC are capable to process salient self-referential auditory stimuli, even in case of absence of behavioural detection of self-conscious processing. We suggest that self-recognition covert brain ability could be an index of consciousness recovery, and thus could help to predict good outcome.